Experimental Evaluation of a Novel Stability Control System for Two-Wheeled Robotic Wheelchairs - Nikpour, Mostafa; Huang, Loulin (Elsevier BV, 2023)
A conventional robotic wheelchair containing four wheels (two active driving wheels and two passive casters) is statically stable with poor manoeuvrability. In comparison, a two-wheeled robotic wheelchair (TWRW) without the support of casters offers much better manoeuvrability but is inherently unstable and requires a stability control. Most stability controllers rely on the driving torques of the wheels which are high in magnitude and result in large energy consumption. Various disturbances in the system also affect the performance of the controller. To address these problems, this paper presents a novel control approach where the stability control is achieved through the motion of a pendulum-like movable mechanism added to the TWRW. A scaled-down TWRW is designed to evaluate the performances of the controllers based on PID control and second order sliding mode control (SOSMC). Experimental results show that under the proposed controller approach, the stability of the TWRW is achieved with much less torque, power, and energy consumption than the conventional control systems.
Keywords: 0306 Physical Chemistry (incl. Structural); 0912 Materials Engineering; 0914 Resources Engineering and Extractive Metallurgy; 4016 Materials engineering